Learning and memory performance following acute intranasal insulin administration in abstinent smokers. (24th January 2018) - Hamidovic, Ajna; Candelaria, Lionel; Rodriguez, Ihsan; Yamada, Mikiko; Nawarskas, James; Burge, Mark R.
Abstract: The highest incidence of relapse to smoking occurs within the first 2 weeks of a cessation attempt. In addition to enhanced nicotine craving, this phase of smoking cessation is also marked by learning and memory dysfunction. Many smokers are not able to overcome these symptoms, and they relapse to smoking shortly after trying to quit. In two clinical studies, we evaluated intranasal insulin for efficacy in improving learning and memory function during nicotine withdrawal. Our first study was a crossover evaluation ( N = 19) following 20 hr of smoking abstinence. Study 2 was a parallel design study ( N = 50) following 16 hr of abstinence. Intranasal insulin (60 IU) dose was administered in both studies and cognitive function was measured using California Verbal Learning Test‐II. Intranasal insulin did not improve learning over the 5 verbal learning trials. In addition, intranasal insulin did not improve either short‐ or long‐delay recall in either study. In summary, the one‐time administration of intranasal insulin does not improve verbal learning and memory in smokers. Whether longer administration schedules may be of benefit should be evaluated in future studies.